The relationship between computer literacy and employee performance at NXP Semiconductor Malaysia / Nurul Izzati Jamal - Jamal, Nurul Izzati (2014)
TI1e purpose of this study was to describe the computer literacy and employee performance level at NXP Semiconductor Malaysia. This study also attempted to determine if there was a relationship between computer literacy and employee performance. In addition, this study also investigate if there were differences in computer literacy and employee perfom1ance levels based on the staff age, computer experience and accessibility to office computer. The respondents of this study consisted of 100 staff in NXP Semiconductor. This study used a questionnaire adopted from previous researcher to measure the computer literacy and employees performance levels. The findings of this study showed that generally the staff in NXP had computer literacy above the intermediate level and high level of job performance. There was a significant relationship between computer literacy level between staff based on age, computer experience and computer accessibility. Younger staff were found to have higher computer literacy as compared to the older. For the staff who attend more computer training also found to have higher computer literacy level. Staff NXP who have more computer experience found to have higher computer literacy compared to those who have Less computer experience. Computer literacy level are higher found to those who had easy access to office computer. It was concluded that it is important to ensure that the staff had attend to computer training and computer facilities to improve their computer literacy level regardless of age, computer experience and computer accessibility.